2014
DOI: 10.1111/nzg.12035
|View full text |Cite
|
Sign up to set email alerts
|

Freshwater geographies: Prospects for an engaged institutional project?

Abstract: Freshwater is increasingly a matter of concern in research, policy and public spheres in New Zealand. Geographers have made diverse and powerful contributions to understanding and performing multiple meanings of water in place. This special issue explores some geographical dimensions to the present political moment around freshwater in New Zealand. Prospects for further explicitly geographical contributions to freshwater discussions are manifold but need to be developed within a coherent value proposition and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 28 publications
(39 reference statements)
0
4
0
Order By: Relevance
“…They warn that the aspirational intent of cultural monitoring can be undermined when it is tied too closely to the norms of ‘state of the environment’ reporting in environmental management. Together, these contributions show why we need to – and how we can – remake freshwater politics by knowing water differently (see also Tadaki & Fuller, 2014).…”
Section: Local Themes With Global Resonancementioning
confidence: 96%
See 1 more Smart Citation
“…They warn that the aspirational intent of cultural monitoring can be undermined when it is tied too closely to the norms of ‘state of the environment’ reporting in environmental management. Together, these contributions show why we need to – and how we can – remake freshwater politics by knowing water differently (see also Tadaki & Fuller, 2014).…”
Section: Local Themes With Global Resonancementioning
confidence: 96%
“…Māori scholar Williams (2006) examined Māori values and ethics in relation to water, and Tipa et al (2009) explored how cross‐cultural research on water can and should be conducted to be empowering for all. Following the uptick of interest in freshwater politics surrounding the first NPSFM in 2011, Blue et al (2012) reported a postgraduate‐convened workshop of geographers attempting to "do freshwater differently", and Tadaki and Fuller (2014) edited a special issue of the New Zealand Geographer on Freshwater Geographies. Geographers have since explored issues as wide ranging as the politics of urban water demand management (Trowsdale et al, 2017), the personification of place in legislation (Warne, 2020) and hegemonic discourses of development predicated on ‘more water’ (Thomas et al, 2020).…”
Section: Water Politics In Focusmentioning
confidence: 99%
“…At the 2014 IAG/NZGS conference, Noel Castree singled out New Zealand geography as offering insights for those seeking to displace gestures towards public engagement and interdisciplinarity with practice‐centred thinking and genuinely enactive research. The New Zealand Geographer has recently carried special issues, one in each of human and physical geography (see Lewis & Rosin and Tadaki and Fuller ) that explore different ways of making and performing relevant, publicly engaged geographies. It has also carried multi‐authored pieces from graduate students that take up issues of disciplinary purpose, working across the discipline and building a new publicly engaged disciplinarity from the bottom up (see Blue et al .…”
mentioning
confidence: 99%
“…Over‐extraction, pollution and dispossession affect daily lives and the health and functioning of environments. But if we want to understand ‘how freshwater is done ’ as Tadaki and Fuller () suggest, then the discipline of geography has much to offer. Notably, ‘the discipline of geography’ spans the social and physical sciences, and freshwater provides an opportunity to bring these fields into closer conversation.…”
mentioning
confidence: 99%